The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5455/jice.20160124113555
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effects of parsley, basil, and chicory aqueous extracts against dexamethasone-induced in experimental rats

Abstract: Aim:The objective of this study is to investigate the hypoglycemic, hypolipidemic, and hepatoprotective effects of the aqueous extract of parsley, basil, and chicory whole plant in normal and dexamethasone (Dex) rats.Materials and Methods:50 female albino rats were used in this study and divided into 5 groups (for each 10). Group (1) fed basal diet and maintained as negative control group. Group (2) received Dex in a dose of (0.1 mg/kg b. wt.). Groups 3, 4, and 5 were treated with Dex along with three differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
(32 reference statements)
1
11
0
Order By: Relevance
“…[ 20 ] Dex-induced hyperlipidemia is related with overproduction of reactive oxygen species (ROS) and oxidative damage in several tissues such as liver. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 20 ] Dex-induced hyperlipidemia is related with overproduction of reactive oxygen species (ROS) and oxidative damage in several tissues such as liver. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative damage and growth retardation may be participating in the effect of corticosteroids therapy on the liver function. [ 21 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…Plant sources are proven to be sources of compounds propitious for the health of humans. Regarding antioxidants; this is correlated with a very contemporary issue of averting tumorous situations (neoplasia) (22,23).…”
Section: Screening Of the Antibacterial Activity By Micro Broth Dilution Assaymentioning
confidence: 99%
“…In the present study four plants (Cichorium intybus Linn., Cucumis melo Linn, Cynomorium coccineum, Cynomorium songaricum) were selected for polyherbal preparation. In the traditional system of medicine different preparations of Cichorium intybus L., commonly known as Chicory or Kasni, have been practiced for digestive and hepatic problems and lower glucose levels and inflammation (22,23). Several studies have reported the antioxidant, inflammation-reducing, and blood-glucose-lowering activities of Cichorium and, to some extent investigating the mechanistic approach also (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%